Fault discrimination and protection coordination for a bipolar full‐bridge MMC‐HVDC scheme. Issue 15 (3rd September 2018) - Wenig, Simon; Goertz, Max; Heinisch, Mike; Suriyah, Michael; Leibfried, Thomas
Abstract : Fault discrimination and protection design for bipolar high‐voltage direct current transmission solutions based on modular multilevel converters (MMC‐HVDC) links are of significant importance for a reliable and resilient power transmission. If full‐bridge submodules are utilised, fault‐dependent handling concepts considering the location of an event are enabled. This study presents a comprehensive approach to differentiate and deal with internal converter and dc side faults. While a multitude of measurements inside and at the clamps of each converter is usually only used for simple threshold‐based hardware‐related protection, additional differential and derivative criteria may further improve selectivity. However, this requires careful configuration to avoid improper reactions. To highlight the coordinated manner of the proposed concept, various faults are analysed and selected examples are explicitly investigated and visualised using the PSCAD EMTDC software.